2018
DOI: 10.1002/ange.201806922
|View full text |Cite
|
Sign up to set email alerts
|

Nido‐Carboranes: Donors for Thermally Activated Delayed Fluorescence

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Recently, organic TADF molecules that possess very small ΔE ST values have emerged as a new class of PSs. 25,71,72 Owing to the extremely small ΔE ST values, TADF molecules can efficiently undergo both intersystem crossing and reverse intersystem crossing processes under ambient conditions, leading to high triplet quantum yields and long-lived delayed fluorescence (∼μs). 27 Consequently, TADF molecules can work as potential photodynamic agents and in time-resolved luminescence imaging (TRLI) and biosensing.…”
Section: Heavy-atom-free Photosensitizers Based On Sulfur-substituted...mentioning
confidence: 99%
“…Recently, organic TADF molecules that possess very small ΔE ST values have emerged as a new class of PSs. 25,71,72 Owing to the extremely small ΔE ST values, TADF molecules can efficiently undergo both intersystem crossing and reverse intersystem crossing processes under ambient conditions, leading to high triplet quantum yields and long-lived delayed fluorescence (∼μs). 27 Consequently, TADF molecules can work as potential photodynamic agents and in time-resolved luminescence imaging (TRLI) and biosensing.…”
Section: Heavy-atom-free Photosensitizers Based On Sulfur-substituted...mentioning
confidence: 99%
“…Recent research has shown that the ICT-based luminescence characteristics of D‒A dyads are dramatically affected by the electronic environment of the o -carborane cage. For example, the photophysical properties are drastically altered by the deboronation of a closo - o -carborane to give a nido - o -carborane (nest-like structure, where one boron atom is removed from the icosahedron) [ 33 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], as the anionic character of the nido -type structure interrupts the ICT transition [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The intrinsic differences between the electronic properties of closo - and nido - o -carboranes have been investigated, providing inspiration as novel molecular scaffolds for chemodosimeter materials.…”
Section: Introductionmentioning
confidence: 99%